The Nazca Drift System – palaeoceanographic significance of a giant sleeping on the SE Pacific Ocean floor. (2nd March 2022) - Calvès, Gérôme; Mix, Alan; Giosan, Liviu; Clift, Peter D.; Brusset, Stéphane; Baby, Patrice; Vega, Mayssa
Abstract: The evolution and resulting morphology of a contourite drift system in the SE Pacific oceanic basin is investigated in detail using seismic imaging and an age-calibrated borehole section. The Nazca Drift System covers an area of 204 500 km 2 and stands above the abyssal basins of Peru and Chile. The drift is spread along the Nazca Ridge in water depths between 2090 and 5330 m. The Nazca Drift System was drilled at Ocean Drilling Program Site 1237. This deep-water drift overlies faulted oceanic crust and onlaps associated volcanic highs. Its thickness ranges from 104 to 375 m. The seismic sheet facies observed are associated with bottom current processes. The main lithologies are pelagic carbonates reflecting the distal position relative to South America and water depth above the carbonate compensation depth during Oligocene time. The Nazca Drift System developed under the influence of bottom currents sourced from the Circumpolar Deep Water and Pacific Central Water, and is the largest yet identified abyssal drift system of the Pacific Ocean, ranking third in all abyssal contourite drift systems globally. Subduction since late Miocene time and the excess of sediments and water associated with the Nazca Drift System may have contributed to the Andean orogeny and associated metallogenesis. The Nazca Drift System records the evolution in interactions between deep-sea currents and the eastward motion of the Nazca Plate through erosive surfaces and sediment remobilization.